Maternity and Labor Markets: Impact of Legislation in Colombia - Natalia Ramírez Bustamante; Ana Maria Tribin Uribe; Carmi\~na O. Vargas (Inter-American Development Bank (IDB), 2015)
This study seeks to determine the impact on female labor outcomes of the amendment to the Colombian labor law that extended maternity leave from 12 to 14 weeks (Law 1468 of July 2011). To identify this impact, labor market outcomes of two groups of women with different fertility rates are compared. The study finds evidence that as a result of the extension of the maternity leave period, women in the high-fertility age group experience an increase in inactivity rates, informality, and self-employment. The study points to the need for a redesign of maternity protection policy that would enable the economic and social costs of bearing children to be shared by both parents and that may generate social change regarding the importance of paternal care.
hdl:11319/6841
Keywords: J08; J2; J3; J7; K31; 330; maternity leave; female labor market; labor regulation